The displaced as guest: A case study of the Yezidis of Iraq and Jacques Derrida’s deconstruction of hospitality - Jackman, Zachary (AUC Knowledge Fountain, 2017)
This thesis examines the Yezidi forced migration crisis by applying Jacques Derrida’s deconstruction of the binary relationships of self and the other (ipseity) and host and guest (hospitality). This approach first uncovers how the application of these categories operates in the Yezidi dilemma. Further, deconstructing the classifications then creates a space for thinking of alternative means of considering identity, foreignness, the hospitality exchange, and competing discourses. With over half of the entire global Yezidi population still living as hosted, forcibly displaced guests after three years, these new windows may provide a better opportunity to critically engage with the emergency situation and its power relationships and give a superior platform for considering durable solutions for the group, such as the prospect of returning home.